Method for biomimetic mineralization of enamel by fluorine synergistic gallic acid stabilized amorphous calcium phosphate nano-cluster
Through the combination of fluorine synergistic calcium phosphate nanocluster reagents stable with gallic acid, the stability and safety issues in bionic mineralization of enamel are solved, and effective bionic mineralization of enamel is achieved, with commercial application potential.
Patent Information
- Application Number
- CN202411309229.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The prior art lacks effective and non-toxic methods to stabilize calcium phosphate nanoclusters, resulting in poor biomimicry mineralization of enamel, and commonly used stabilizers will change chemical composition or reduce biosafety, affecting commercial applications.
A stable amorphous calcium phosphate nanocluster reagent combination of fluorine synergistic gallic acid is prepared by mixing a specific molar ratio of gallic acid and calcium ion solution, and slowly adding fluorine-containing phosphate ion solution to prepare stable calcium phosphate nanoclusters. Combined with anhydrous ethanol treatment and saliva immersion, bionic mineralization of tooth enamel is achieved.
The bionic mineralization of enamel has been achieved, forming a structure with similar chemical composition and mechanical properties to natural enamel, which has great commercial promotion value and is of great help in the treatment of micro-deficiencies of enamel, early caries and white enamel spots, and it is not Good toxicity and stability.
Smart Images

Figure CN119185367A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tooth enamel repair, and in particular to a method for biomimetic mineralization of tooth enamel using amorphous calcium phosphate nanoclusters stabilized by fluoride and gallic acid. Background Art
[0002] Tooth enamel is a highly mineralized extracellular matrix and the hardest tissue in the human body. Its main component is 95wt%-97wt% nanorod-shaped hydroxyapatite (HA) crystals. Tooth enamel has good mechanical properties, and its excellent mechanical properties come from the highly ordered spatial structure, which plays an important role in controlling the mechanical strength of teeth and acts as a buffer to protect teeth. Caries, trauma, abrasion and improper brushing methods can cause enamel defects. Mature tooth enamel is a non-living tissue, and the damaged part can hardly repair itself.
[0003] At present, metal, dental composite resin and ceramic materials are commonly used in clinical practice to fill and repair defective enamel. However, these materials have weak mechanical strength, poor adhesion to teeth and are easy to fall off. Their physical properties and chemical composition are different from those of natural materials in the human body. In order to achieve a perfect repair of the defect with chemical composition and structure similar to natural enamel, biomimetic mineralization repair of enamel is currently an ideal strategy. Based on the in-depth exploration and understanding of biominerals, it is found that the growth front of many biominerals during formation is mainly amorphous minerals fused on crystalline minerals for an epitaxial growth. In this process, amorphous calcium phosphate plays a vital role as a precursor for the entire mineralization process. In the bionic nature, constructing a biomimetic mineralization front on the surface of enamel for the repair of enamel is a mainstream strategy. At present, the strategy of constructing a biomimetic mineralization front is mainly achieved by constructing polymer-stabilized calcium phosphate nanoclusters (PNCs). Calcium phosphate precursors such as PNCs are mainly obtained by the dual decomposition of calcium salts and phosphates in liquid media. However, PNCs are very unstable due to their large surface atomic ratio, large specific surface area, and large surface energy. They tend to agglomerate and will be transformed into large-sized crystals (such as HA, etc.) within a short period of synthesis. Scientists mainly stabilize PNCs by adding stabilizers. Additives that can stabilize precursors such as PNCs can be divided into two categories: organic and inorganic. Inorganic stabilizers mainly include magnesium ions, strontium, fluoride ions, pyrophosphate ions, and citrate ions. However, the stabilizing effect of inorganic stabilizers is not good, and their addition will also change the chemical composition of precursors such as ACP nanoparticles, forming calcium phosphates doped with magnesium, strontium, etc., and may also reduce their biological safety. The organic stabilizers that have been studied more include organic macromolecular stabilizers (polyethylene glycol, polyvinyl alcohol, and polyacrylic acid) and organic small molecule stabilizers (triethylamine, etc.). Since tooth enamel is basically pure minerals, a large amount of organic matter will be introduced when repairing enamel with polymer-stabilized calcium phosphate clusters, which will destroy the structural integrity of the enamel repair layer and greatly reduce the mechanical strength of the enamel. Therefore, polymer-stabilized calcium phosphate clusters are not suitable for enamel repair. Organic small molecule stabilizers such as triethylamine can bring excellent mechanical strength and bionic structure, but organic small molecules such as triethylamine are toxic and easily react with phosphate to deposit and remain on the teeth, which is not suitable for clinical application. In addition, the most critical problem is that both macromolecular stabilizers and small molecule stabilizers have poor ability to stabilize calcium phosphate clusters when used, and have a short shelf life. If the product is made into a product with a very short shelf life, it will greatly affect its commercial application. Therefore, it is urgent to further study the stabilizers and formulations of calcium phosphate nanoclusters to further improve the effect of enamel mineralization repair. Summary of the invention
[0004] The present invention aims to provide a reagent combination for biomimetic mineralization of enamel by using fluorine and gallic acid to stabilize amorphous calcium phosphate nanoclusters, so as to solve the technical problem that the prior art lacks an effective and non-toxic method and system for promoting the stability of calcium phosphate nanoclusters to achieve biomimetic mineralization of enamel.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A reagent combination for biomimetic mineralization of tooth enamel, the reagent combination comprising a gallic acid-calcium phosphate-fluoride solution, the raw materials of which comprise gallic acid, a calcium ion source, a phosphorus ion source and a fluoride ion source; the molar ratio of the calcium element in the calcium ion source to the gallic acid is 0.01-0.5, and the molar ratio of the calcium element in the calcium ion source to the phosphorus element in the phosphorus ion source is 0.1-5.
[0007] Furthermore, the gallic acid-calcium phosphate-fluoride solution is prepared by the following method: dissolving gallic acid in water to obtain a gallic acid solution; adding a calcium ion source to the gallic acid solution under stirring to obtain a gallic acid-calcium solution; dissolving a phosphorus ion source and a fluoride ion source in water to obtain a fluorine-containing phosphorus ion source solution, and dropwise adding the fluorine-containing phosphorus ion source solution to the stirring gallic acid-calcium phosphate solution, and adjusting the pH value to obtain a gallic acid-calcium phosphate-fluoride solution.
[0008] Furthermore, the mass fraction of gallic acid in the gallic acid solution is 0.01-2%; in the gallic acid-calcium solution, the concentration of calcium is 0.01-30mM; in the fluorine-containing phosphorus ion source solution, the concentration of phosphorus is 0.01-30mM, and the concentration of fluorine is 10ppm-1500ppm.
[0009] Further, gallic acid is dissolved in water and stirred at 35-50° C. for 10-120 min to obtain a gallic acid solution.
[0010] Further, under the stirring condition of >300 rpm, a calcium ion source is added to the gallic acid solution and stirred for 10-120 min to obtain a gallic acid-calcium solution.
[0011] Further, the fluorine-containing phosphorus ion source solution is added dropwise at a rate of 1-4 drops / second to the gallic acid-calcium solution being stirred at >300 rpm, with a pH value of 5-7, to obtain a gallic acid-calcium phosphate-fluoride solution.
[0012] Furthermore, the reagent combination also includes artificial saliva or saliva.
[0013] Furthermore, the reagent combination also includes a washing solution; the washing solution includes anhydrous ethanol and water.
[0014] The technical solution also provides an application of a reagent combination for biomimetic mineralization of enamel in the preparation of a drug for promoting enamel mineralization. The drug for promoting enamel mineralization includes a gallic acid-calcium phosphate-fluoride solution and a washing solution; the washing solution includes anhydrous ethanol and water.
[0015] Furthermore, the gallic acid-calcium phosphate-fluoride solution is used to contact the tooth enamel to be repaired, and then the tooth enamel is washed with anhydrous ethanol and water in sequence and then contacted with saliva or artificial saliva.
[0016] The principle and beneficial effects of this technical solution are:
[0017] This technical solution provides a practical combination and method for biomimetic mineralized enamel that can be clinically applied and has great commercial promotion value. By mixing gallic acid and calcium ion solution in a specific molar ratio, and then slowly adding a fluoride-containing phosphate ion solution to the pre-mixed solution, stable calcium phosphate nanoclusters (PNCs) can be prepared, and the demineralized enamel is treated with PNCs with added fluoride. After naturally drying in the air, the treated enamel is cleaned with anhydrous ethanol and then immersed in artificial saliva or saliva to achieve directional transformation and growth of HA crystals on the surface of the enamel to be biomimetic mineralized, forming a structure with chemical composition and mechanical properties similar to natural enamel, which can well realize the biomimetic mineralization of enamel. This method has great potential for realizing the clinical transformation of enamel biomimetic mineralization strategies, and is of great help in treating oral problems such as enamel micro-defects, early caries and enamel white spots.
[0018] This scheme is adopted, and in the presence of fluoride, calcium phosphate nanoclusters stabilized by gallic acid are used, and then treated with anhydrous ethanol to construct a relatively pure biomimetic mineralized enamel front, thereby realizing the biomimetic mineralization of enamel. The general process is as follows: dissolving calcium ion source compounds and gallic acid in water to obtain gallic acid-calcium solution; dissolving phosphate and fluoride ion source compounds in water to obtain fluoride-added phosphorus source solution; slowly dropping the fluoride-containing phosphorus source solution into the gallic acid-calcium solution being stirred to obtain GA-CaP-F solution (calcium phosphate nanoclusters containing gallic acid and fluoride ions), i.e., fluoride-added gallic acid-stabilized calcium phosphate nanoclusters (PNCs); treating demineralized enamel with GA-CaP+F solution for a certain period of time; contacting the enamel with saliva or artificial saliva for a period of time, and using this method, the biomimetic mineralization of enamel can be realized.
[0019] Gallic acid is a cheap, edible compound. The above process can well realize the biomimetic mineralization of tooth enamel. This method has great potential for realizing the clinical transformation of tooth enamel biomimetic mineralization strategy, and is very helpful for treating oral problems such as enamel micro-defects, early caries and enamel white spots. At present, there are no studies and patent reports on the use of gallic acid as a stabilizer to construct PNCs, nor are there any studies and patent reports on the use of fluorine synergistically gallic acid-stabilized PNCs to achieve enamel biomimetic mineralization through anhydrous ethanol treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the surface morphology of natural enamel in Example 1 (scale: 10 μm).
[0021] Figure 2 This is a scanning electron microscope image of the surface morphology of natural tooth enamel in Example 1 (scale: 5 μm).
[0022] Figure 3 This is a scanning electron microscope image of the surface morphology of natural tooth enamel after acid etching in Example 1 (scale: 10 μm).
[0023] Figure 4 This is a scanning electron microscope image of the surface morphology of natural tooth enamel after acid etching in Example 1 (scale: 5 μm).
[0024] Figure 5 This is a scanning electron microscope image of the surface morphology of the mineralized enamel in Example 1 (scale: 10 μm).
[0025] Figure 6 This is a scanning electron microscope image of the surface morphology of the mineralized enamel in Example 1 (scale: 5 μm).
[0026] Figure 7 This is a scanning electron microscope image of the surface morphology of the mineralized enamel of Example 2 (scale: 10 μm).
[0027] Figure 8 This is a scanning electron microscope image of the surface morphology of the mineralized enamel in Example 2 (scale: 5 μm).
[0028] Fig. 9 This is a scanning electron microscope image of the surface morphology of the mineralized enamel of Example 3 (scale: 10 μm).
[0029] Fig.10 This is a scanning electron microscope image of the surface morphology of the mineralized enamel of Example 3 (scale: 5 μm).
[0030] Fig.11 This is a scanning electron microscope image of the surface morphology of the mineralized enamel of Example 4 (scale: 10 μm).
[0031] Fig.12 This is a scanning electron microscope image of the surface morphology of the mineralized enamel of Example 4 (scale: 5 μm).
[0032] Fig.13 This is a scanning electron microscope image of the surface morphology of the mineralized enamel of Example 5 (scale: 10 μm).
[0033] Fig.14 This is a scanning electron microscope image of the surface morphology of the mineralized enamel in Example 5 (scale: 5 μm).
[0034] Fig.15 This is a statistical diagram of the hardness of mineralized enamel obtained by different treatment methods in the examples.
[0035] Fig.16 Statistical graph of carbon content on the surface of mineralized enamel obtained by different treatment methods in the examples. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.
[0037] The overall technical process of this technical solution is as follows:
[0038] A reagent combination for biomimetic mineralization of tooth enamel includes gallic acid (GA), a calcium ion source, a phosphorus ion source and a fluoride ion source, wherein the molar ratio of calcium in the calcium ion source to GA in the gallic acid solution is 0.01-0.5, and the molar ratio of calcium in the calcium ion source to phosphorus in the phosphorus ion source is 0.1-5.
[0039] The calcium ion source is at least one of calcium chloride, calcium nitrate, and calcium acetate; the phosphorus ion source is at least one of phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, potassium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate. Deionized water is used as a solvent to prepare various solutions.
[0040] At room temperature, gallic acid is added to water, and stirred for 10-120min (preferably 30min) in a water bath at 35-50°C (preferably 45°C) to prepare a GA aqueous solution, and then a calcium ion source is added thereto, and a magnetic stirrer (500rpm, which needs to be ensured to be above 300rpm, and the upper limit depends on the equipment used, for example: 20000rpm) is stirred for 10-120min (preferably 60min) to obtain a GA-Ca aqueous solution. At room temperature, a phosphorus ion source and a fluoride ion source are added to water to obtain a fluorinated phosphate solution. At room temperature, a magnetic stirrer (500rpm, which needs to be ensured to be above 300rpm, and the upper limit depends on the equipment used, for example: 20000rpm) is stirred, and the fluorinated phosphate solution is slowly added to the GA-Ca aqueous solution (2 drops / second). The pH value is adjusted to 5-7 (preferably 5.5) to obtain a GA-CaP-F solution (a solution containing gallic acid, a calcium ion source, a phosphorus ion source, and a fluoride ion source). The GA-CaP-F solution is applied to the enamel to be repaired, and the excess liquid is absorbed by filter paper and then placed in the air to dry naturally, and then rinsed with anhydrous ethanol for 1-5 minutes (preferably 3 minutes), followed by water washing for 1 minute. In the above manner, the mass percentage of GA in the prepared GA solution is 0.01-2wt%; the calcium concentration in the prepared GA-Ca solution is 0.01-30mM; the phosphorus concentration in the prepared fluoride-added phosphate solution is 0.01-30mM, and the fluorine concentration is 10ppm-1500ppm.
[0041] A reagent combination for biomimetic mineralized enamel also includes saliva or artificial saliva. Artificial saliva is a conventional reagent in the prior art of the art, and commercial artificial saliva can be purchased or prepared by oneself. In the present technical solution, the specific formula of artificial saliva used is: 1.5mM CaCl2·2H2O, 0.9mM K2HPO4, 15ppm F - , 130mM KCL, 1mM NaN3, prepared with 20mM HEPES buffer, and adjusted the solution pH to 7.00±0.03. Artificial saliva is a conventional reagent in this field. Artificial saliva of other formulas can also be used in actual use, mainly to provide calcium and phosphorus elements to simulate the effect of saliva. After applying GA-CaP-F solution to treat enamel, the enamel needs to be further mineralized in the environment of saliva or artificial saliva to form a sufficient mineralization layer. Because the subsequent experiments were carried out in enamel samples, artificial saliva was specifically used. Soak the enamel after GA-CaP-F solution, anhydrous ethanol and water washing, place it in saliva or artificial saliva for soaking, and replace fresh artificial saliva every 6 hours for a total of 72-144 hours.
[0042] Example 1
[0043] (1) Preparation of enamel specimens
[0044] The enamel of healthy bovine teeth with soft plaque, tartar and soft tissue removed was cut into pieces of 0.5×0.5×0.2 cm. 3 Prepare 5 enamel slices of different sizes for each sample. Use 360-mesh, 1200-mesh, 3000-mesh and 5000-mesh SiC sandpaper to grind the slices in sequence until the surface is smooth and flat. Keep the slices moist during the whole process.
[0045] The enamel slice was inverted in the dental mold and embedded with the denture base resin. After solidification, the enamel slice was demolded, and then the surface of the enamel slice was ground to be on the same surface as the resin. Ultrasonic cleaning was carried out in water for 20 minutes. After natural drying in the air, the surface of the tooth sample was covered with a windowed polyester tape to create a test area of about 3×6mm 2 , use a hardness tester to test its hardness, which is the hardness of natural tooth enamel. The scanning electron microscope image of natural tooth enamel is shown in Figure 1 and Figure 2 .
[0046] The prepared enamel slices were immersed in 37% phosphoric acid and allowed to stand for 40 seconds, washed with water for 1 minute, and ultrasonically treated for 20 minutes. The hardness after acid etching was measured with a digital hardness tester, and the surface morphology of the enamel after acid etching was measured with a scanning electron microscope. The surface morphology of the enamel after acid etching is shown in Figure 3 and Figure 4 The acid-etched enamel slides were stored in deionized water at 4°C and air-dried before use.
[0047] (2) GA-CaP-F solution
[0048] At room temperature, 29.7 ml of deionized water was taken, 0.40 g of gallic acid (molecular weight 170.12, about 0.00235 mol) was added thereto, and the mixture was stirred in a water bath at 45° C. for 30 min to prepare a 1% GA solution, to which 0.0173 g of CaCl2·2H2O (molecular weight 147.01, the concentration of calcium in the GA-Ca solution was about 0.000118 mol / 29.7 ml) was added, and the mixture was stirred for 60 minutes with a magnetic stirrer (500 rpm), at which time the molar ratio of calcium ions to GA was 0.05; at room temperature, 10 ml of deionized water was taken, 0.01 g of Na2HPO4 (molecular weight 141.96, the concentration of phosphorus in the fluorinated phosphate solution was about 0.00007 mol / 10 ml) and 0.004 g of NaF (molecular weight 41.99, the concentration of F in the fluorinated phosphate solution was 180 ppm) were added thereto to obtain a fluorinated phosphate solution. The fluorinated phosphate solution was slowly added to the GA-Ca aqueous solution (2 drops / second) under stirring with a magnetic stirrer (500 rpm) at room temperature. The pH value was adjusted to 5.5 with 1 M NaOH. The molar ratio of CaCl2·2H2O / Na2HPO4 in the final solution was about 1.67, and a GA-CaP-F solution was obtained.
[0049] Use a small dental cotton swab to dip a small amount of GA-CaP-F and apply it to the demineralized (acid-etched) enamel slice for 5 minutes. More specifically, use an ordinary cotton swab to fully soak the GA-CaP-F solution (saturated dipping), and then use the soaked cotton swab to wipe the dentin surface, and wipe back and forth for 2.5 minutes. Then, use a new cotton swab to dip the GA-CaP-F solution and wipe the enamel slice again once, that is, apply it to the dentin surface for a total of 5 minutes. Use filter paper to absorb the excess liquid around the dentin, and after the liquid is fully dried (naturally dried in the air), rinse with anhydrous ethanol for 3 minutes and wash with water for 1 minute. Then, place the dentin with the surface coated with GA-CaP-F solution facing down in 37°C artificial saliva, keeping the surface of the dentin coated with GA-CaP solution in full contact with the artificial saliva. Replace fresh artificial saliva every 6 hours. After 72 hours, use a digital hardness tester to measure the hardness after mineralization, and use a scanning electron microscope to measure the surface morphology of the mineralized enamel. For details, see Figure 5 and Figure 6 .
[0050] Example 2
[0051] The preparation of enamel specimens, acid etching, and artificial saliva are the same as in Example 1. In this example, we do not add gallic acid solution to the treatment steps of the enamel specimens to observe the biomimetic mineralization of the enamel after acid etching. That is, take 29.7 ml of deionized water, add 0.0173 g of CaCl2·2H2O to it, and stir it with a magnetic stirrer (500 rpm) for 60 minutes to obtain a calcium ion source solution, and use the calcium ion source solution instead of GA-Ca solution to carry out subsequent steps. The CaP-F solution finally obtained is used to treat tooth enamel (instead of GA-CaP-F solution, and no gallic acid is added), and other operations are the same as in Example 1. The electron microscope scanning image of the enamel after biomimetic mineralization is detailed in Figure 7 and Figure 8 .
[0052] Example 3
[0053] The preparation of enamel specimens, acid etching, and artificial saliva are the same as in Example 1. In this example, we do not add fluoride to the phosphorus source solution in the treatment step of the enamel specimens to observe the biomimetic mineralization of the enamel after acid etching. That is, take 10 ml of deionized water, add 0.01 g of Na2HPO4 thereto, and obtain a phosphate solution to replace the phosphate solution with fluoride. The GA-CaP solution finally obtained is used to treat tooth enamel (instead of GA-CaP-F solution, without adding fluorine element), and other operations are the same as in Example 1. The electron microscope scanning image of the enamel after biomimetic mineralization is detailed in Fig. 9 and Fig.10 .
[0054] Example 4
[0055] The preparation of enamel specimens, acid etching, and artificial saliva are the same as in Example 1. In this example, we removed the absolute ethanol water washing step from the enamel specimen processing steps to observe the biomimetic mineralization of enamel after acid etching. That is, the enamel slices were treated with GA-CaP-F solution, dried, and directly washed with water for 1 minute without using absolute ethanol for rinsing. The other operations were the same as in Example 1. The electron microscope scanning image of the biomimetic mineralized enamel is shown in detail. Fig.11 and Fig.12 .
[0056] Example 5
[0057] The preparation of enamel specimens and acid etching and the preparation of artificial saliva are the same as in Example 1. In this example, based on Example 1, the calcium source solution is replaced with calcium nitrate and the phosphorus source solution is replaced with sodium phosphate to observe the biomimetic mineralization of enamel after acid etching. The details are as follows:
[0058] At room temperature, take 29.7 ml of deionized water, add 0.40 g of GA thereto, stir in a 45°C water bath for 30 min to prepare a 1% GA aqueous solution, then add 0.0193 g of Ca(NO3)2 (molecular weight 164.09, the concentration of calcium in the GA-Ca solution is about 0.000118 mol / 29.7 ml), stir with a magnetic stirrer (500 rpm) for 60 minutes, at which time the molar ratio of calcium ions to GA is 0.05; at room temperature, take 10 ml of deionized water, add 0.0115 g of Na3PO4 (molecular weight 164, the concentration of phosphorus in the fluorinated phosphate solution is about 0.00007 mol / 10 ml) and 0.004 g of NaF (molecular weight 41.99, the concentration of F in the fluorinated phosphate solution is 180 ppm) thereto to obtain a fluorinated phosphate solution. At room temperature, under the stirring action of a magnetic stirrer (500 rpm), the fluorinated phosphate solution was slowly added to the GA-Ca aqueous solution (2 drops / second). The pH value was adjusted to 5.5 with 1M NaOH to obtain a GA-CaP-F solution. The Ca(NO3)2 / Na3PO4 in the final solution was 1.67. Other operations were the same as in Example 1. The electron microscope scanning image of the biomimetic mineralized enamel is shown in detail. Fig.13 and Fig.14 .
[0059] Based on the experimental results of Examples 1-5: the surface of the natural enamel flakes has a fuzzy scaly structure, the cross section is neat, and the enamel columns with a prismatic structure of about 5 μm in cross-sectional diameter are highly parallel to each other along the c-axis direction (the long axis of the apatite crystal) ( Figure 1 , 2 After acid etching, the scaly structure of the enamel surface became clear, the enamel interstitium was largely damaged, the enamel prisms became sparse, and the enamel fibers were incomplete and scattered ( Figure 3 , 4 After being treated in Example 1, the mineralized layer grew epitaxially along the enamel column, presenting a dense structure layer perpendicular to the surface. The scale-like structure clearly visible after acid etching was completely covered, and the surface became smooth and flat, which was closer to the surface structure of natural enamel ( Figure 5 , 6 After the treatment of Example 5, similar results as those of Example 1 were obtained ( Fig.13 , 14 ), indicating that changing the anion type of the calcium source and phosphorus source has little effect on the method results. In Example 2, after removing gallic acid, the enamel surface after acid etching is covered with a layer of material, but there is no orderly structure, which is quite different from the natural enamel surface structure ( Figure 7 , 8 In Example 3, without the addition of fluoride, the mineralized layer showed a sparse fibrous structure and was relatively messy ( Fig. 9 , 10In Example 4, the anhydrous ethanol washing step was removed, and the mineralized layer was thin and had no effective ordered structure ( Fig.11 , 12 ).
[0060] The hardness of the mineralized dentin samples obtained in the examples and comparative examples, and the dentin samples before and after acid etching were measured using a hardness tester (the dentin was pretreated with the GA-CaP solution, CaP-F solution or GA-CaP-F solution prepared in each example and comparative example, and the dentin samples were taken out for hardness testing after continuing to be treated with artificial saliva for 72 hours). For each dentin sample, the initial natural dentin, acid-etched dentin, and mineralized dentin were measured using a digital hardness tester. For each measurement, 3 points were selected for measurement on the same dentin sample, and the average value of the 3 measurement points was taken as the hardness of the dentin sample. 9 dentin samples were measured for each example or comparative example, and the table shows the average hardness of the 9 dentin samples for each example or comparative example. For details of the experimental results, see Fig.15 , in the figure, **** indicates that the two groups of data were analyzed by ordinary one-way analysis of variance, p < 0.0001; ns indicates that there is no significant difference between the two groups of data; hardness is Vickers hardness HV. The hardness of natural enamel is 328.10 ± 10.73; the hardness of natural enamel after acid etching decreases to 131.4 ± 13.65; after the treatment of Example 1, the hardness is restored to 334.9 ± 18.78, which is not significantly different from the hardness of natural enamel. The hardness of Example 2 is increased to 233.1 ± 21.60 after acid etching, but due to the lack of gallic acid, there is still a significant difference in hardness from natural enamel. The hardness of the mineralized layer of Example 3 is significantly reduced to 218.6 ± 26.92, but due to the lack of fluoride ions, there is a significant difference in hardness from natural enamel. The hardness of the enamel of Example 4 is 225.6 ± 19.86; the hardness of the enamel of Example 5 is 330.4 ± 22.72. In Example 4, the anhydrous ethanol cleaning step is removed, and the mineralization effect is not ideal, resulting in that the hardness of the bionic mineralized enamel cannot be effectively improved.
[0061] The hardness data of Examples 1, 2, and 3, and the acid-etched enamel were compared. After the enamel was treated with GA-CaP-F solution (containing gallic acid, fluoride ions, and calcium phosphate nanoclusters), the hardness of the enamel was increased by 334.9-131.4=203.5; after the enamel was treated with CaP-F solution (containing fluoride ions and calcium phosphate nanoclusters), the hardness of the enamel was increased by 233.1-131.4=102.7; after the enamel was treated with GA-CaP solution (containing gallic acid and calcium phosphate nanoclusters), the hardness of the enamel was increased by 218.6-131.4=87.2. It can be seen that the effect of improving the hardness of tooth enamel using GA-CaP-F solution (using fluoride ions and gallic acid at the same time) (203.5) is stronger than the sum of the effects of improving the hardness of tooth enamel using fluoride ions and gallic acid respectively (102.7+87.2), indicating that the combined use of fluoride ions and gallic acid, in the presence of calcium phosphate nanoclusters (CaP), produces a synergistic effect in improving the hardness of biomimetic mineralized tooth enamel. In addition, the ethanol cleaning step is very critical, otherwise, the synergistic effect of fluoride ions and gallic acid is difficult to play (Example 4).
[0062] After scanning with EDS equipped with a scanning electron microscope, it was found that the carbon content of Example 4 reached 13.08±1.99, which was significantly different from the carbon content of natural enamel 3.27±0.36. In other examples, after ethanol cleaning, the carbon content was not significantly different from that of natural enamel ( Fig.16 ). Therefore, ethanol washing for 1-5 minutes is a key technical point for improving the hardness of bionic mineralized enamel and ensuring that the carbon content maintains a natural level.
[0063] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A reagent combination for biomimetic mineralization of tooth enamel, characterized in that: The reagent combination comprises a gallic acid-calcium phosphate-fluoride solution, and the raw materials of the gallic acid-calcium phosphate-fluoride solution comprise gallic acid, a calcium ion source, a phosphorus ion source and a fluoride ion source; the molar ratio of the calcium element in the calcium ion source to the gallic acid is 0.01-0.5, and the molar ratio of the calcium element in the calcium ion source to the phosphorus element in the phosphorus ion source is 0.1-5.
2. The reagent combination for biomimetic mineralization of tooth enamel according to claim 1, characterized in that: The gallic acid-calcium phosphate-fluoride solution is prepared by the following method: dissolving gallic acid in water to obtain a gallic acid solution; adding a calcium ion source into the gallic acid solution under stirring to obtain a gallic acid-calcium solution; dissolving a phosphorus ion source and a fluoride ion source in water to obtain a fluorine-containing phosphorus ion source solution; dropping the fluorine-containing phosphorus ion source solution into the stirred gallic acid-calcium solution, and adjusting the pH value to obtain a gallic acid-calcium phosphate-fluoride solution.
3. A reagent combination for biomimetic mineralization of tooth enamel according to claim 2, characterized in that: The mass fraction of gallic acid in the gallic acid solution is 0.01-2%; in the gallic acid-calcium solution, the concentration of calcium element is 0.01-30mM; in the fluorine-containing phosphorus ion source solution, the concentration of phosphorus element is 0.01-30mM, and the concentration of fluorine element is 10ppm-1500ppm.
4. The reagent combination for biomimetic mineralization of tooth enamel according to claim 3, characterized in that: Dissolve gallic acid in water and stir at 35-50° C. for 10-120 min to obtain a gallic acid solution.
5. The reagent combination for biomimetic mineralization of tooth enamel according to claim 4, characterized in that: Under stirring conditions of >300 rpm, a calcium ion source is added to the gallic acid solution and stirred for 10-120 min to obtain a gallic acid-calcium solution.
6. The reagent combination for biomimetic mineralization of tooth enamel according to claim 5, characterized in that: The fluorine-containing phosphorus ion source solution is added dropwise at a rate of 1-4 drops / second to the gallic acid-calcium solution being stirred at >300 rpm, with a pH value of 5-7, to obtain a gallic acid-calcium phosphate-fluoride solution.
7. The reagent combination for biomimetic mineralization of tooth enamel according to claim 6, characterized in that: It also includes artificial saliva or saliva.
8. The reagent combination for biomimetic mineralization of tooth enamel according to claim 7, characterized in that: It also includes a washing liquid; the washing liquid includes anhydrous ethanol and water.
9. Use of a reagent combination for biomimetic mineralization of tooth enamel according to any one of claims 1 to 8 in the preparation of a drug for promoting tooth enamel mineralization, characterized in that: Drugs that promote enamel mineralization include gallic acid-calcium phosphate-fluoride solution and washing solution; the washing solution includes anhydrous ethanol and water.
10. Use of the reagent combination for biomimetic mineralization of tooth enamel according to claim 9 in the preparation of a drug for promoting tooth enamel mineralization, characterized in that: The gallic acid-calcium phosphate-fluoride solution is used to contact the tooth enamel to be repaired, and then the tooth enamel is washed with anhydrous ethanol and water in sequence and then contacted with saliva or artificial saliva.
Citation Information
Patent Citations
Combination for repairing dental enamel and method for preparing fluorapatite by using the same
CN101843560A
Application of epigallocatechin gallate in protecting dentin
CN103830115A
Preparation method of enamel remineralizing liquid
CN107753301A
Method for constructing biomimetic mineralization enamel of biomimetic mineralization leading edge by instantly mixing calcium ion source and phosphorus ion source
CN116139022A
Dental glaze-like ordered structure hydroxyapatite as well as preparation method and application thereof
CN117618254A